High-potency statin and ezetimibe use and mortality in survivors of an acute myocardial infarction: a population-based study. Issue 11 (19th February 2014) - Pauriah, Maheshwar; Elder, Douglas H J; Ogston, Simon; Noman, Awsan Y S; Majeed, Azeem; Wyatt, Jeremy C; Choy, Anna-Maria; MacDonald, Thomas M; Struthers, Allan D; Lang, Chim C
Abstract : Objective: To determine all-cause mortality in patients with a first myocardial infarct who were treated with simvastatin compared with high-potency statin and simvastatin/ezetimibe combination. Background: Despite statin use, residual cardiovascular risk remains. Therapeutic options include more potent statins or addition of ezetimibe. There is no clinical outcome data on the use of ezetimibe in such patients. Methods: Retrospective longitudinal study using the United Kingdom General Practice Research Database. Patients who had survived 30 days after their first acute myocardial infarct (AMI), had not received prior statin or ezetimibe therapy and were started on a statin within 30 days of AMI were included. Three groups were identified according to their follow-up: (i) simvastatin monotherapy; (ii) high-potency statin group (patients who started on simvastatin and switched to atorvastatin or rosuvastatin); and (iii) ezetimibe/statin combination group (patients who received ezetimibe in addition to statin). Results: 9597 patients (57% male, mean age of 65±13 years) matched study criteria: simvastatin (n=6990 (72.8%)); high-potency statin (n=1883, (19.6%)); and ezetimibe/statin combination (n=724 (7.5%)). During a mean follow-up of 3.2 years, there were 1134 (12%) deaths. In the multivariate proportional hazards model, the adjusted HR for high-potency statin and ezetimibe group were 0.72 (95% CI 0.59 to 0.88, p<0.001) and 0.96 (95% CI 0.64 to 1.43, p=0.85), respectively. A similar result was also obtained in the propensity score analysis that took into account covariates that predicted drug treatment groups. Conclusions: Patients switched to a high-potency statin had a significantly reduced mortality compared with simvastatin monotherapy. There was no observed mortality benefit in the ezetimibe group.